Quantifying the suppression of the (un)-obscured star formation in galaxy cluster cores at 0.2≲ z ≲0.9. Issue 1 (7th February 2019) - Rodríguez-Muñoz, L; Rodighiero, G; Mancini, C; Pérez-González, P G; Rawle, T D; Egami, E; Mercurio, A; Rosati, P; Puglisi, A; Franceschini, A; Balestra, I; Baronchelli, I; et al.
ABSTRACT: We quantify the star formation (SF) in the inner cores (R / R 200 ≤0.3) of 24 massive galaxy clusters at 0.2≲ z ≲0.9 observed by the Herschel Lensing Survey and the Cluster Lensing and Supernova survey with Hubble . These programmes, covering the rest-frame ultraviolet to far-infrared regimes, allow us to accurately characterize stellar mass-limited (M_*10^10 M ⊙ ) samples of star-forming cluster members (not)-detected in the mid- and/or far-infrared. We release the catalogues with the photometry, photometric redshifts, and physical properties of these samples. We also quantify the SF displayed by comparable field samples from the Cosmic Assembly Near-infrared Deep Extragalactic Legacy Survey. We find that in intermediate- z cluster cores, the SF activity is suppressed with respect the field in terms of both the fraction (F ) of star-forming galaxies (SFGs) and the rate at which they form stars (SFR and sSFR = SFR/M_* ). On average, the F of SFGs is a factor ∼2 smaller in cluster cores than in the field. Furthermore, SFGs present average SFR and sSFR typically ∼0.3 dex smaller in the clusters than in the field along the whole redshift range probed. Our results favour long time-scale quenching physical processes as the main driver of SF suppression in the inner cores of clusters since z ∼0.9, with shorter time-scale processes being very likely responsible for a fraction of the missing SFG population.